A Study on Clinico-Pathological Profile of Breast Cancer Patients and Their Correlation With Uterine Fibroids Using Hormone Level and Receptor Status Assessment. (April 2022) - Mohan, Anjaly; Kumar, Vinay; Brahmachari, Swagata; Pandya, Bharati
Purpose: To study the clinico-pathological profile of breast cancer patients and the prevalence of uterine fibroids in them, their hormonal levels and hormone receptor status. Patients and methods: 52 patients with breast cancer who attended AIIMS Bhopal from November 2018 to January 2020 were selected, with their clinical details, triple assessment and other investigations for further management being performed and recorded. The presence of uterine fibroids was assessed using ultrasound of the abdomen, and for patients who had undergone hysterectomy, previous medical records were examined to ascertain the history of uterine fibroids. Serum levels of estrogen and progesterone were assessed using chemi-luminescent micro-particle immune assay (CMIA). Results: The mean age of patients was 50.35 ± 10.87 years. 36.54% of our patients had uterine fibroids, of whom 15.38% had undergone hysterectomy for the same, and 21.15% was detected on ultrasound of the abdomen during evaluation. Among patients with uterine fibroids, 84.2% were hormone receptor-positive, while in patients without uterine fibroids, only 57.6% had positive receptors. ( P  = 0.049). Among premenopausal patients, there was a statistically significant difference in serum progesterone values between patients with and without uterine fibroids. Conclusion: The prevalence of uterine fibroids in our study group of breast cancer patients was found to be high. The role of estrogen and progesterone in the pathophysiology of both diseases and the common risk factors involved may biologically explain this finding. Breast cancer and other estrogen associated disorders may hold future research prospects.